Policy Implementation Analysis of Village-Owned Enterprises (Bumdes) in Empowering the Local Economy in Garut Regency - Meliana, Mila; Kania, Ikeu; Akbar, Gugun Geusan; Ulumudin, Aceng (Ilomata International Journal of Social Science, 2025)
This study aims to explore implementing BUMDes policies in the Garut Regency, which has not yet been fully effective due to various influencing factors. The research adopts a qualitative approach with a descriptive method. Data was collected through interviews with the DPMD and BUMDes managers in the Garut Regency and analysis of relevant documents. Implementing BUMDes policies in Garut Regency demonstrates varying outcomes, influenced by key factors such as stakeholder communication, resource availability, implementer disposition, and bureaucratic structure. Referring to Edward III's theory, the success of BUMDes policy implementation is shaped by four main variables: (1) Communication, which ensures that policies are well understood and accepted by the village community and BUMDes managers; (2) Resources, including funding, human resources, and infrastructure essential for the sustainability of BUMDes; (3) Disposition (Implementer Attitude), reflecting the commitment of local government, BUMDes managers, and the community in executing policies; and (4) Bureaucratic Structure, involving coordination between agencies and administrative procedures that affect the smooth execution of policies. The research findings reveal that despite challenges such as limited human resources and restricted access to capital, well-managed BUMDes have the potential to strengthen the local economy and reduce dependence on central government assistance. Enhancing communication, building human resource capacity, and streamlining bureaucracy are crucial in accelerating village economic empowerment goals through BUMDes.